Students Competence in Solving Hots Math Problems Studied from Adversity Quotient - Atikah Devi Rusmohandi; Fitri Alyani (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
Solving HOTS math problems requires high-level thinking skills that also requires students to have high level adversity quotient in order to solve HOTS-type problems. This research aims to study and describe the competence level of elementary school students in solving HOTS math problems and to identify how students from various types of adversity quotient competences solve HOTS math problems. This research is a descriptive qualitative one using case study method. The research population was one of elementary schools in South Jakarta area, while the research sample was 110 fifth- grade students. The research sample was determined using non-probability sampling. Instruments used were essay tests, adversity quotient questionnaires, and interview guidelines. The research shows a result that on the average, elementary school students are categorized as camper-type of adversity quotient in which camper-type students are able to understand problems but have not yet able to plan a strategy for solving it, while quieter-type students are not able to meet all indicators in HOTS problem solving. Keywords: Problem Solving Competence, High Order Thinking Skill (HOTS), Adversity Quotient.